Corruption and Foreign Direct Investment - Habib, Mohsin; Zurawicki, Leon (Journal of International Business Studies, 2002)
This study examines the impact of corruption on foreign direct investment (FDI). First, the level of corruption in the host country is analyzed. Second, the absolute difference in the corruption level between the host and home country is examined. The analysis provides support for the negative impacts of both. The results suggest that foreign investors generally avoid corruption because it is considered wrong and it can create operational inefficiencies.